La difesa della morale come giustificazione di limitazioni al rispetto della vita privata, nella giurisprudenza della Corte europea dei diritti umani (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The Author describes how the European Convention authorizes limits to rights and liberties, in particular by mentioning the protection of morals in article 8, the logic and problems of the margin of national appreciation and of the European consensus, with at the end the awkward recognition by the Court of the conclusive role of the majorities in the countries.
Keywords: European Convention on Human Rights; respect for private life; protection of morals; margin of appreciation; European consensus